The Routledge handbook of pronouns
1 online resource (xxii, 496)
Keywords: This original volume provides the first state-of-the-art overview of research on pronouns in the 21st century. With its dedicated sections on grammar, history, and change, language learning/acquisition, cognition and comprehension, power, politics, and identity, The Routledge Handbook of Pronouns shows that contemporary interest in pronouns and gender represents just the tip of the iceberg. Led by Laura Paterson, a transdisciplinary collection of experts discuss the global history of different pronoun systems, synthesize the literature, and contextualize the salient issues and current debates shaping research on pronouns across different spheres and via different theoretical-methodological traditions. The Handbook is designed to encourage readers to engage with a range of perspectives from within and beyond their immediate areas of interest, with the ultimate aim of shaping the future trajectory of interdisciplinary, multiingual research on pronouns. Using data from multiple languages and engaging deeply with the social, cultural, political, technological, and psychological factors that can influence pronoun use, this innovative book will be an indispensable resource to scholars and advanced students of theoretical and applied linguistics, education, and the social and behavioural sciences.